A insurgência do maravilhoso na fotografia contemporânea: notas sobre o antropozoomorfismo, uma manifestação em imagens - Monteiro, Taís Marques (2019)
In this dissertation, we perceive in the images of a group of contemporary Latin American photographers, Flor Garduño, Graciela Iturbide, Marcos López, Rodrigo Braga and Sofia Borges, the possible encounters with the marvelous, creative faculty of acceptance of the rationally unexplainable phenomena that in Latin America. As a method, we construct intuitive assemblies of planks that approximate, by rhythm and sensitivity, the photographs. Concomitantly, with a micrological look, we look for epistemological traces in the visuality of the photographs, described in a sensorial and phenomenological way. We think about the issues of contemporary photography related to the conception of creation of worlds and of fiction, close to Phillipe Dubois, Georges Didi-Huberman, André Rouillé, Ronaldo Entler and Susan Sontag. The questions related to the marvelous erupt from the thought of Irlemar Chiampi, Alejo Carpentier, Tzevan Todorov, among other theorists. The anthropozoomorphism, a manifestation of the marvelous in photography, is delineated as a line of force that provokes the appearance of sparks of knowledge from the evidence that is shown in the photographic images